Pengaruh Massage Uterus Terhadap Penurunan Tinggi Fundus Uteri Sebagai Upaya Pencegahan Perdarahan - Lina Contesa (Jurnal Ventilator, 2023)
Postpartum hemorrhage is a frequent cause of death in mothers with 1,280 cases. One of the causes of postpartum bleeding is a uterus that does not contract or is called uterine atony. Uterine atony keeps the blood vessels open so that blood continues to flow. Efforts to make the uterus contract are by uterine massage. Uterine massage helps make the blood vessels close and stimulates contractions so that the height of the fundus decreases, indicating that the uterus is slowly shrinking. Research objective: to determine the effect of uterine massage on reducing the height of the uterine fundus as an effort to prevent post-partum bleeding. Method: This research uses a quasi-experimental design, namely post test control group design. The sample in this study was part of normal postpartum mothers at BPM. The sample was divided into a treatment group and a control group. The sampling technique uses purposive sampling. Data were analyzed using the unpaired sample t test. The results of the independent t test obtained a p value of 0.071 (p > 0.05). This means that there is no effect of uterine massage on reducing the height of the uterine fundus.